Specificity of acclimated biodecolourisation culture to cosubstrate structure - Rakmi Abdul Rahman,; Mohd Ariffin Aton,; Jailani Salihon, (1990)
Experiments on using acclimated culture were carried out to determine if compounds other than glucose could be effective as cosubstrate in biodecolourisation of an azo dye. The role of cosubstrate was found to be not structure dependent hence cometabolism was not likely to be involved in biodecolourisation. This finding also offers opportunities for use of carbon sources other than glucose and for mixing of wastewaters to facilitate biodecolourisation